Study of the Function of City Parks as Public Open Space in Meuraxa District, Banda Aceh - Farisa Sabila; Putri Aryastiana (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Parks are part of Green Open Space (RTH) and Public Non-Green Open Space (RTNH) which are used to carry out various activities such as recreation, education, and sports. Meuraxa sub-district has a public green space area of 11.442 Ha with types of parks, green lanes, green belts, and cemeteries under the maintenance and management of the Banda Aceh City Government [1]. Green spaces in Meuraxa Sub-district is currently utilized for recreation, education, sports, and various social interaction activities. This research was conducted to identify the function of the Meuraxa District park based on its characteristics and community perceptions related to the existing park functions. The analysis in this study used scoring method, descriptive statistical method and descriptive method. The sampling method used in this research is non-probability sampling technique with purposive sampling type with a total sample of 100 respondents. This research has assessed the overall condition of the park which shows a fairly good level of optimality. Some key indicators, such as cleanliness, availability of facilities, and visitor comfort, have met the expected standards. The results of surveys and observations show that this park has become a place of interest and is often visited by the community. However, some parks in the study locations still do not meet the appropriate standards and the utilisation is not optimal in terms of ecological, social, aesthetic, and economic aspects